2013
DOI: 10.1534/g3.113.005835
|View full text |Cite
|
Sign up to set email alerts
|

The Biotinidase Gene Variants Registry: A Paradigm Public Database

Abstract: The BTD gene codes for production of biotinidase, the enzyme responsible for helping the body reuse and recycle the biotin found in foods. Biotinidase deficiency is an autosomal recessively inherited disorder resulting in the inability to recycle the vitamin biotin and affects approximately 1 in 60,000 newborns. If untreated, the depletion of intracellular biotin leads to impaired activities of the biotin-dependent carboxylases and can result in cutaneous and neurological abnormalities in individuals with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Mutation analysis revealed that this boy was homozygous for c.98_104 del7insTCC; p.C33FfsX36 in the BTD gene [6]. This mutation is a relative common mutation in Western European countries and results in a frameshift and the synthesis of a truncated, inactive enzyme protein causing profound biotinidase deficiency.…”
Section: Case Studiesmentioning
confidence: 94%
“…Mutation analysis revealed that this boy was homozygous for c.98_104 del7insTCC; p.C33FfsX36 in the BTD gene [6]. This mutation is a relative common mutation in Western European countries and results in a frameshift and the synthesis of a truncated, inactive enzyme protein causing profound biotinidase deficiency.…”
Section: Case Studiesmentioning
confidence: 94%
“…Mutation in BTD gene leads to altered enzyme activity. There are nearly 165 mutations have been reported in literature so far [16]. We could not genotype our cases as this facility was not available at our centre.…”
Section: Discussionmentioning
confidence: 99%
“…Biotinidase deficiency is an autosomal recessive disease, and more than 165 different mutations have been identified [8]. In the present case, the brother of the newborn was homozygotic for biotinidase deficiency and harboring two different mutations, one from each parent as both parents were heterozygotic carriers of the disease.…”
Section: Discussionmentioning
confidence: 67%